Health maps and the contemporary visibility regime - Ibiapina, Érico; Bernardes, Anita (Saúde e Sociedade, 2019)
This article analyzes the articulation between territory, access, and technologies in health. The objective is to analyse the health map based on the relationship between visibility regime and health surveillance technologies. The course ofreflection is based on the problematization of the use of the georeferencing in the field of health for the monitoring and surveillance of people circulation flows in urban space as a bio-political strategy. The analysis,therefore, involves the problematization of mapping techniques in the health field to think of forms of population control and regulation as unnatural processes that allow certain forms of articulation between access, territory, and health technologies. In this way, the article follows the itinerary: (1) analyses the territory as one of the elements that constitute a device in the field of health; (2) discusses how surveillance is implicated in health mapping strategies from the first biosocial maps; (3) approaches the relationship between georeferencing and surveillance technologies as biopolitical strategy.